Right Ventricular Septal Pacing to Produce Narrow QRS Duration in Patient with High Degree 2:1 AV Block - Santoso, Michael; Setiadi, Benny; Rampengan, Starry H.; Jim, Edmond L. (Universitas Sam Ratulangi, 2025)
Prolonged right ventricular (RV) apical pacing has been recognized to be associated with progressive left ventricular (LV) dysfunction. This impairment of LV function resultant from RV apical pacing is a remodelling process consequent to abnormal ventricular activation and contraction. RV septal pacing theoretically is associated with a more physiological ventricular activation results in shorter electrical activation delay and consequently less mechanical dyssynchrony. We reported A-75-year-old woman presented to emergency department (ED) with dyspnea only on exertion in the last 3 weeks before admission, she also complaint near syncope episode while doing activities. Electrocardiogram (ECG) result was high degree AV block with 2:1 conduction with ventricular rate 40 beats per minute. PPM implantation was performed with VVIR mode, ventricle lead inserted into mid-septal RV. ECG post implantation showed pacing rhythm with narrow QRS duration. Pacemaker-related LBBB is associated with an adverse prognosis. RV septal pacing produces more synchronous contraction denoted by narrow QRS, preventing the deterioration of LV structure and function. RV septal pacing, although not as good as intrinsic conduction or His bundle pacing, may be more desirable for chronic RV pacing compared to the RV apex as a narrow QRS is associated with improved LV dynamics. RV septal pacing was safely done in this patient, but further study needed to evaluate its long-term effect. Keywords: AV block; permanent pacemaker; septal; right ventricle